If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5X + -4Y + -7) = 0 Reorder the terms: -1(-7 + 5X + -4Y) = 0 (-7 * -1 + 5X * -1 + -4Y * -1) = 0 (7 + -5X + 4Y) = 0 Solving 7 + -5X + 4Y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -5X + -7 + 4Y = 0 + -7 Reorder the terms: 7 + -7 + -5X + 4Y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5X + 4Y = 0 + -7 -5X + 4Y = 0 + -7 Combine like terms: 0 + -7 = -7 -5X + 4Y = -7 Add '-4Y' to each side of the equation. -5X + 4Y + -4Y = -7 + -4Y Combine like terms: 4Y + -4Y = 0 -5X + 0 = -7 + -4Y -5X = -7 + -4Y Divide each side by '-5'. X = 1.4 + 0.8Y Simplifying X = 1.4 + 0.8Y
| 132-r=209 | | (5/x-3)+1=(30/x^2-9) | | -4-q=-7 | | d+36=18 | | m-18=54 | | 9+d=15 | | 4-m=9 | | 3+5=2(4x+1)-7 | | 2xm=12 | | 8x-25x=8 | | 4+1/4y=-5 | | -120-5x=0 | | (3/x-1)=(5/x+2) | | 3(x+7)=19+3x | | 6(q+3)=-24 | | 7-13= | | 7t+2t=-36 | | A^2-13K-6=0 | | 5m+11=14+2m | | 9-(1+x)=2 | | 8d-7=16-3d | | (f+6)+3=7 | | 3m-7=2m-9 | | 4(4x+1)-3x-4(6-8)+8= | | -5(2r-14)=-1 | | x-4-7x=20 | | -7(8-3M)=5 | | 8=12+(x+1) | | 20-(10/(2x1)) | | y^2-5y+32=0 | | 13x^8+18x= | | 27z^6+(-23u)= |